2010
DOI: 10.1002/pon.1684
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cancer and quality of life for post‐treatment non‐Hodgkin lymphoma survivors

Abstract: Objective-Recent work suggests that perceptions of the impact of cancer on survivors' lives are associated with physical and mental health and quality of life (QOL) outcomes. This study examines the association between the Impact of Cancer version 2 scales (IOCv2) and these outcomes in a large sample of survivors of adult non-Hodgkin lymphoma (NHL).Methods-Participants completed a mailed survey to assess physical and mental health (SF-36), cancer-specific quality of life (FACT-G) and perceived impact of cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
81
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 21 publications
15
81
1
1
Order By: Relevance
“…Moreover, because another study using the same dataset found this relationship to be significant among colorectal cancer survivors [26], additional analyses on specific genders and races of colorectal cancer survivors are warranted. With regard to social support, this study supports evidence from previous research that higher social support is associated with higher mental HRQoL [22,[37][38][39] and suggests that this association is not unique to either gender.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, because another study using the same dataset found this relationship to be significant among colorectal cancer survivors [26], additional analyses on specific genders and races of colorectal cancer survivors are warranted. With regard to social support, this study supports evidence from previous research that higher social support is associated with higher mental HRQoL [22,[37][38][39] and suggests that this association is not unique to either gender.…”
Section: Discussionsupporting
confidence: 90%
“…Correlates of poorer physical and mental HRQoL among survivors include lack of a partner [15], low socioeconomic status (SES) [15][16][17][18], advanced cancer stage [19,20], invasive or systemic treatments [20,21], shorter time since diagnosis [18], and increased frequency of comorbidities and symptoms [15,[20][21][22]. Age affects each domain of HRQoL differently, with older age negatively correlating with physical HRQoL [18] and younger age negatively correlating with mental HRQoL [15].…”
Section: Introductionmentioning
confidence: 97%
“…However, it should be mentioned as other studies (for example [18]) showed that education was not associated with QoL. Finally, as already described elsewhere [1,12,15,17,18,23,24], those who reported having other health problems showed a worse quality of life in all domains considered (except in Mental health, in the present study).…”
Section: Discussionsupporting
confidence: 48%
“…[8][9][10][11][12] In the last decades, more attention is being paid to HRQOL after cancer diagnosis. Some studies have investigated HRQOL and fatigue in NHL survivors, [13][14][15][16][17][18][19][20][21] but almost all used a cross-sectional approach (only one measurement at a defined time). 13,[17][18][19][20][21] However, the longitudinal course of fatigue and HRQOL in patients with NHL and their return to normal life remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have investigated HRQOL and fatigue in NHL survivors, [13][14][15][16][17][18][19][20][21] but almost all used a cross-sectional approach (only one measurement at a defined time). 13,[17][18][19][20][21] However, the longitudinal course of fatigue and HRQOL in patients with NHL and their return to normal life remains largely unknown. The aims of the present study were, therefore, to: (i) assess fatigue and HRQOL twice following primary treatment, (ii) compare fatigue and HRQOL with an age-and sex matched normative population to assess the severity of the concerns, and (iii) identify associations with fatigue in survivors who remained fatigued.…”
Section: Introductionmentioning
confidence: 99%